1988
DOI: 10.1002/anie.198808421
|View full text |Cite
|
Sign up to set email alerts
|

1,3,4,6‐Tetraamino‐2,5‐diazapentalenes: Delocalized Antiaromatic Compounds

Abstract: As we have shown through several examples, combinations of donor and acceptor substituents stabilize cyclopolyenes containing (4n) 7c electrons. They may even take on the properties of arenes (e.g., positive resonance energies)."] The question of double-bond delocalization in such systems could only be approached so far for diethyl 2,4-bis(diethylamino)cyclobutadiene-1 , 3 -d i~a r b o x y l a t e ;~~-~~ in contrast to tetra-tert-butylcyclobutadiene,'5,61 it exhibits a "benzene-like" double-bond delocalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 27 publications
1
4
1
Order By: Relevance
“…Azapentalenes and diazapentalenes have also been reported in the literature. 65–67 Omar et al recently identified an amine-substituted cyclopenta[ c ]pyrrole, 68 however, we find its E (S 1 –T 2 ) to be +43 meV at the EOM-CCSD/aug-cc-pVDZ level. There are several substituted pyrrolo[3,4- c ]pyrroles that exhibit Hund's rule violations between S 1 and T 2 , which are listed in Fig.…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…Azapentalenes and diazapentalenes have also been reported in the literature. 65–67 Omar et al recently identified an amine-substituted cyclopenta[ c ]pyrrole, 68 however, we find its E (S 1 –T 2 ) to be +43 meV at the EOM-CCSD/aug-cc-pVDZ level. There are several substituted pyrrolo[3,4- c ]pyrroles that exhibit Hund's rule violations between S 1 and T 2 , which are listed in Fig.…”
Section: Resultscontrasting
confidence: 70%
“…21,49,50 The balance between p-distortivity and s-rigidity can be pushed towards doublebond delocalization, and several substituted pentalenes and structurally analogous indacenes assume high symmetry in their crystal structures. 47,[51][52][53][54] Several alternative explanations to double-bond delocalization in crystal structures have been suggested, 51,[55][56][57] and the assignment of the correct global minimum structures continues to be a computational challenge when the energy difference is small. [57][58][59] Considering the ongoing challenge of assessing the true global minimum energies, our focus here is to assess excited-state energy ordering in substituted molecules where double-bond localization is minimized.…”
Section: Resultsmentioning
confidence: 99%
“…Within experimental error, the diazapentalene moiety is planar (mean deviation 0.003 A Ê ), with atom O1 (which forms weaker out-of-plane hydrogen bonds to adjoining anions) having the largest deviation [0.245 (2) A Ê ]. A comparison of the metrical parameters of the diazapentalene anion with those of the corresponding neutral and cationic moieties shows that, as in the previous example (Butcher et al, 2003), the largest changes occur in the bond distances to the aza N atom [N1ÐC2 = 1.3364 (16) A Ê compared with average values of 1.3765 and 1.3885 A Ê found for the neutral (Closs et al, 1988) and cationic (Virnekaes et al, 2001) moieties, respectively]. Due to the shortening of the CÐN bonds in the ®ve-membered rings there is a corresponding increase in the exocyclic angle (C2ÐC1ÐC2 H ) to the extremely large value of 151.18 (17) , the same as was seen in the previous example (Butcher et al, 2003).…”
supporting
confidence: 55%
“…A large singlet-triplet splitting for a formal biradical, as displayed in Table 3 for the heterosubstituted molecules, was found in the recently prepared di-tert-butyl derivative of 2,5-diamino-1,4-benzoquinonediimine, which exists in a persistent zwitterionic form in the singlet ground state. 23,24 Apart from tetraphenylthieno(3,4-c)thiophene (IIe), [14][15][16] there is no experimental evidence for molecules IIb-d or their derivatives (though Closs et al reported 25 experimental evidence for II with X ) N) nor for IIIb-d, but crystal structures of potassium and ammonium salts of the dianion of 1,3,4,6tetranitro-2,5-diazapentalene have been published. 26,27 Compound VI, 7,8-diazapentalene, is the least stable diazapentalene isomer, nevertheless its derivatives were obtained and the crystal structures of nitro-substituted-7,8-diazapentalenes were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from tetraphenylthieno(3,4-c)thiophene (IIe), there is no experimental evidence for molecules IIb−d or their derivatives (though Closs et al reported experimental evidence for II with X = N) nor for IIIb−d, but crystal structures of potassium and ammonium salts of the dianion of 1,3,4,6-tetranitro-2,5-diazapentalene have been published. , Compound VI, 7,8-diazapentalene, is the least stable diazapentalene isomer, nevertheless its derivatives were obtained and the crystal structures of nitro-substituted-7,8-diazapentalenes were reported. , …”
Section: Discussionmentioning
confidence: 99%